Strontium isotopes measurement from bunker cave system: a contribution for the multi-proxy paleoclimate research of Central Europe - Stumpf, Cintia Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In recent years speleothem has been intensely studied due to its great potential of registering paleoclimate proxies but some considerably uncertaintiesregarding speleothem proxy interpretation still exist. In order to minimize these uncertainties, multi-proxy approach has been used. Here is presented the strontium isotope record from Bunker cave, northwest Germany. This cave was previously studied and has proved well record paleoclimate changes during Holocene for central Europe.87Sr/86Sr ratio is presented for rain water, A-horizon soil (water and leachate), C-horizon soil (water and leachate), host rock and host rock leachate, drip water and from a stalagmite (Bu4) previously dated covering the Holocene. Upper soil presented the higher values in contrast with host rock (lower values). Drip water and C-horizon presented intermediated ratios. Sr isotopesare used to track the source of 87Sr/86Sr in the Bunker system, resulting in a mixture between A-horizon soil, C-horizon soil and host rock. A decreasing trend in Bu4 indicates change in the Sr source in the system

Nos últimos anos espeleotemas tem sido intensamente estudados devido ao seu grande potencial de registro de proxies paleoclimáticas, mas ainda existem algumas incertezas consideráveis em relação à interpretação das proxies em espeleotemas. A fim de minimizar estas incertezas, aproximação multi-proxy tem sido utilizada. Aqui é apresentado o registro isótopos de estrôncio da caverna Bunker, noroeste da Alemanha. Esta caverna foi previamente estudada e provou registrar bem mudanças paleoclimáticas durante o Holoceno na Europa central. Razão de 87Sr/86Sr é apresentada para a água da chuva, horizonte A do solo (agua e solução lixiviada), horizonte C do solo (áua e solução lixiviada), rocha hospedeira e lixiviado da rocha, água de gotejamento e de uma estalagmite (Bu4) previamente datada, cobrindo o Holoceno. O solo orgânico apresentou os valores mais elevados, em contraste com a rocha hospedeira (valores de razão menores). Água de gotejamento e horizonte-C do solo apresentaram índices intermediários. Isótopos de Sr são utilizados para rastrear a fonte de 87Sr/86Sr no sistema Bunker, resultando em uma mistura entre o horizonte A do solo, horizonte C do solo e rocha hospedeira. Uma tendência descendente na Bu4 indica mudança na fonte de Sr no sistema
Keywords: Espeleologia; Estroncio; Carste; Paleoclimatologia; Intemperismo; Europa Central